Uji Aktivitas Antijamur Ekstrak Beberapa Jenis Biota Laut terhadap Aspergillus flavus LINK dan Penicillium sp. LINK - HUTASOIT, SANGGUL; SUADA, I KETUT; SUSRAMA, I GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.2, No.1, Januari 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Study of Anti fungi E xtract of S ome T ypes of Marine Biota to the Apergillus flavus LINK. and Penicillium sp. LINK. The purpose of this study is to know the effectiveness of marine biota, namely Aglaophenia sp., Eucheuma cottonii, Sargassum sp., Gracilaria sp., and Ulva sp. in impeding the growth of Aspergillus flavus and Penicillium sp. fungi which is isolated from contaminated corn seed. The results of this study shown that the crude extract of marine biota is very effective in impeding the growth of Aspergillus flavus and Penicillium sp . fungi. Extract which is capable forming the greater impeding zone is Aglaophenia sp, that is 68,20 mm to Penicillium sp. with very strong category of impeading power. Aglaophenia sp. ekstract shown a greater empeading power to the colony of fungi, that is 49,40% to Aspergillus flavus and 49,20% to Penicillium sp. Keywords: Marine Biota, A nti fungi , Aspergillus flavus , and Penicillium sp .